Assesing wave power potential in Nkhatabay, Malawi - David Khumbanyiwa (Energy Justice, 2024)
Background: This thesis is an investigation of the wave power resource on Lake Malawi, precisely Nkhatabay, focusing on the spatial distribution of wave power of the said places exposed to the highest wave power. Findings: The main objective of this study was to determine the wave potential of Lake Malawi in Malawi in order to allow design and usage of wave energy in Malawi. Methods: The study methodology employed to achieve this main objective entails an analysis of measured wave data recorded at wave recording station along Lake Malawi. Conclusion: The analysis provided a general description of wave power at the location for which wave data exist. From this analysis,it was found that Nkhatabay is exposed to average wave power of approximately 202 KW/m annually. Data was collected from the Department of Climate Change and Meteorological Services (DCCMS), who have implanted a Lake buoy at Usisya in Nkhatabay. The data gathered was analyzed using Microsoft excel and R studio to come up with graphs for proper description of results. Power calculations were conducted as well to determine the output of turbines used with respect to the wave data observed.